Shawqi Deif’s Reformative Approach to Arabic Grammar Pedagogy for Non-Native Learners - Setiadi, Fadlan Masykura (JURNAL IJ-ATL, 2022)
This study aims to examine Shawqi Deif's views on the renewal of Arabic grammar teaching for non-Arab speakers as outlined in his book Renewing Grammar and analyze his efforts in presenting grammar materials more effectively. The research method used is a literature review by analyzing the contents of the book Renewing Grammar and other relevant works to understand the idea of grammar renewal proposed by Shawqi Deif. The results of the study indicate that Shawqi Deif has several main views in grammar renewal, such as eliminating irrelevant discretionary and local parsing, limiting parsing to aspects that help understanding, establishing more accurate definitions and controls for certain grammatical elements, and adding relevant materials while removing elements that are considered redundant. In his book, Deif presents grammar materials systematically, covering aspects of pronunciation, verb and noun conjugation, nominative, accusative, complement cases, and additional elements such as mention, deletion, and differentiation based on context. This study is expected to provide insight into Shawqi Deif's reform approach which can be a reference for developing a more contextual and efficient Arabic grammar teaching curriculum for non-Arab learners.